The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12909-022-03552-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical students describe their wellness and how to preserve it

Abstract: Background Despite widespread efforts to create wellness programming in medical schools, there is a paucity of literature examining students’ perception of wellness and perceptions of these programs. With the inaugural class at the Arizona campus of Mayo Clinic Alix School of Medicine (MCASOM-AZ), an opportunity arose to establish an empirically evaluated wellness curriculum that most inclusively and effectively enables medical students to flourish for years to come. The initial wellness offeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Increased awareness of professional burnout, depression among doctors, and mental health problems beginning during their college years has focused researchers' attention on the mental well-being of medical students (Chatterjee et al, 2022). According to research, medical students are more likely to suffer from mental illness, substance abuse and professional burnout compared to other students (Klein & McCarthy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Increased awareness of professional burnout, depression among doctors, and mental health problems beginning during their college years has focused researchers' attention on the mental well-being of medical students (Chatterjee et al, 2022). According to research, medical students are more likely to suffer from mental illness, substance abuse and professional burnout compared to other students (Klein & McCarthy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…19,23,28,29 Skills-based longitudinal wellness curricula have emerged as a new area of intervention, but there is scant research exploring their effectiveness and medical students' valuation of them. 1,30,31 In a recent mixed-methods study conducted at the Mayo Clinic Alix School of Medicine-AZ, an examination of their multifaceted wellness curriculum, including curriculum-embedded seminars, a wellness committee, student-driven programming, and mental health services, was undertaken. 30,31 The results outlined in the initial publication of this study indicated a decrease in perceived stress and an increase in overall well-being over the course of the academic year, with no significant difference in outcomes between medical students who participated in the wellness curriculum and those who did not.…”
Section: Introductionmentioning
confidence: 99%
“…1,30,31 In a recent mixed-methods study conducted at the Mayo Clinic Alix School of Medicine-AZ, an examination of their multifaceted wellness curriculum, including curriculum-embedded seminars, a wellness committee, student-driven programming, and mental health services, was undertaken. 30,31 The results outlined in the initial publication of this study indicated a decrease in perceived stress and an increase in overall well-being over the course of the academic year, with no significant difference in outcomes between medical students who participated in the wellness curriculum and those who did not. 30 Furthermore, students' responses revealed that unscheduled time (e.g., protected time away from academic activities) had the most significant impact on their well-being, followed by student-led activities as the second-most influential factor.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Although these efforts are laudable, trainees can feel uncomfortable with structured wellness activities that are embedded in the curriculum, as individual definitions of mental wellness are heterogeneous. 4 Thus, there is a preference among trainees for student-led wellness activities, which tend to emphasise a diverse conceptualisation of mental wellness. 4 In this light, student-led wellness activities are one of many tools that can facilitate healthy coping via the safe discussion and normalisation of mental health struggles.…”
mentioning
confidence: 99%
“… 4 Thus, there is a preference among trainees for student-led wellness activities, which tend to emphasise a diverse conceptualisation of mental wellness. 4 In this light, student-led wellness activities are one of many tools that can facilitate healthy coping via the safe discussion and normalisation of mental health struggles. Ultimately, further research and system-level change are needed to address both the mental wellness crisis and the discomfort with formal wellness interventions among trainees.…”
mentioning
confidence: 99%